2023
DOI: 10.3390/ani13071258
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Performance of Triplet-Bearing Ewes on Commercial Farms and Research Priorities Identified by Sheep Producers to Improve the Survival of Triplet-Bearing Ewes and Their Lambs

Abstract: Consultation with sheep producers was used to quantify the mortality of triplet-bearing ewes and their lambs, identify management practices adopted by producers to reduce these losses and prioritise future research needs to improve the survival of triplet-bearing ewes and their lambs. Surveys were completed by 64 producers across Australia who identified and separated triplet-bearing ewes from twin-bearing ewes in 2017 and/or 2018. On average, 5.9% of all ewes mated were identified as carrying triplets (6.6% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Responses to these challenges will always be founded on solid science, and the solutions will be diverse and multidisciplinary, as will the opportunities for research. Rather than offer an impossible list, I will confine my suggestions to research in reproduction: (i) Olfactory memory in the context of both the male effect and mother-young bonding; (ii) DoHaD and epigenetics, perhaps the ‘hottest’ current topic in reproductive biology; (iii) Embryo mortality, traditionally a very difficult research topic but now vulnerable to new tools for quantifying and investigating the problem; (iv) Postnatal survival, often dismissed as a problem confined to multiple births, but multiple births will be essential in future production systems, so it is time to take on the challenge ( 49 ). Importantly, the 100% CGE model ( 16 ) is not going to be applicable to all industries in all geographical or socio-economic environments, but individual aspects of the model can be introduced in a planned process ( 50 , 51 ) that needs to be supported by local applied research.…”
Section: Opportunities For Research In Cge Managementmentioning
confidence: 99%
“…Responses to these challenges will always be founded on solid science, and the solutions will be diverse and multidisciplinary, as will the opportunities for research. Rather than offer an impossible list, I will confine my suggestions to research in reproduction: (i) Olfactory memory in the context of both the male effect and mother-young bonding; (ii) DoHaD and epigenetics, perhaps the ‘hottest’ current topic in reproductive biology; (iii) Embryo mortality, traditionally a very difficult research topic but now vulnerable to new tools for quantifying and investigating the problem; (iv) Postnatal survival, often dismissed as a problem confined to multiple births, but multiple births will be essential in future production systems, so it is time to take on the challenge ( 49 ). Importantly, the 100% CGE model ( 16 ) is not going to be applicable to all industries in all geographical or socio-economic environments, but individual aspects of the model can be introduced in a planned process ( 50 , 51 ) that needs to be supported by local applied research.…”
Section: Opportunities For Research In Cge Managementmentioning
confidence: 99%
“…The number of lambs weaned per ewe joined under pastoral systems, such as in Australia and New Zealand, has risen by 10 to 20% over the last twenty years [ 4 , 5 ]. However, a consequence of greater fecundity is an increase in the number of triplet-bearing ewes within a flock [ 6 , 7 ]. Triplet-born lambs are smaller at birth, can be metabolically challenged, and receive less colostrum and milk than their twin counterparts, contributing to lower survival to weaning [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Triplet-born lambs are smaller at birth, can be metabolically challenged, and receive less colostrum and milk than their twin counterparts, contributing to lower survival to weaning [ 8 ]. In addition, although data are somewhat sparse, triplet-bearing ewes themselves have lower survival during late-pregnancy and in lactation compared to single- and twin-bearing ewes [ 7 , 9 ], and this lower survival has a negative impact on lamb survival [ 5 , 7 ]. Australian producers who scanned their ewes for triplets were surveyed in 2018 and reported that the average mortality of triplet-bearing ewes between pregnancy scanning and marking was 6.4% and ranged from 0 to 27%, regardless of breed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations